PENERAPAN DESAIN ERGONOMIS MESIN POLES UNTUK KERAJINAN PERAK “UNGGA CREATIVE) UNTUK MENUNJANG PARIWISATA DI DESA UNGGA, KECAMATAN PRAYA BARAT DAYA, KABUPATEN LOMBOK TENGAH - I Made Adi Sayoga; Made Wijana; I Nyoman Nugraha Ardana Putra; I Wayan Joniarta; Rizky Fathullah; Ilham Maulana Akbar (Universitas Mataram, 2023)
Ungga Village, Praya Barat Daya District, is a well-known silver craft center in Central Lombok. Featured products are: brooches, rings, studs, hairpins, suweng, pendants, bracelets and brooches-pendants. The jewelry is made from a combination of pearl shells which are shaped into oval, round, oblong, rectangular, triangular and half round shapes and then tied/framed with silver ornaments. PKM partner